Migration, entrepreneurship and development: Critical questions - Wim Naudé; Melissa Siegel; Katrin Marchand (IZA Journal of Migration, 2017)
This paper poses and answers a number of critical questions about the relationship between migration and entrepreneurship in the process of economic development. In doing so, we show that the standard policy response to migrants and migrant entrepreneurs are often based on an inadequate understanding of migrant entrepreneurs. The questions we pose are the following: (i) Are immigrants really more entrepreneurial than natives? (ii) Are migrant remittances likely to fund entrepreneurship in their home countries? (iii) Are return migrants more likely to be entrepreneurial than non-migrants? And finally, based on the answers, (iv) Does migration matter for development? We conclude that one must avoid seeing migrants as super-entrepreneurs and that the (positive) developmental impact of migration is more significant through other channels. Removal of discriminatory barriers against migrants and against migrant entrepreneurs in labour, consumer and financial markets will promote development in both sending and receiving countries, not least through reducing the shares of migrants that are reluctant entrepreneurs.
Keywords: J60; L26; O15; F22; 330; Migration; Entrepreneurship; Development; Remittances